Research of indexes of physical development, physical preparedness and functional state of student of 10-11 years under the influence of engagement in rugby-5 - Філенко, Л. В.; Філенко, І. Ю.; Мартиросян, А. А. (Physical Education Theory and Methodology, 2012)
A height, weight, speed, adroitness, force and speed-power internalss, is investigational, indexes of the functional state of the cardiovascular system of students of 10-11 years which taking the lessons of physical culture of rugby-5. In research 52 students of 5th forms of the Kharkiv gymnasium took part 172. Expediency of the use of rugby-5 engagement physical culture at secondary school is grounded. The basic indexes of physical preparedness of schoolchildren of 10-11 years are considered. Dependence of indexes of physical development is established, physical preparedness and functional state of the cardiovascular system of organism of pupils under impact of taking up rugby-5.